The Significance of Investing in School Facilities and Measures for Reform - Sungmin Han (Korea Development Institute (KDI), 2017)
Voices are being raised over the need to improve Korea's educational environment for the health and safety of our students. And despite the fact that the educational environment plays a vital role in both learning and teaching, investment in school facilities has been given low priority. In response, the new government has laid out plans to reform neglected and aged school facilities, emphasizing the duty of the nation with respect to education investment. In this context, relevant policies should focus on the importance of investment in school facilities. - Investment in school facilities has been a low priority due to policy decisions and a shift in the distribution of financial resources. - Policies for the investment in school facilities should aim to provide safe and positive educational environments for students. - Evaluation of the educational environment should include not only indicators for teaching conditions but also that for school facilities. - One out of three elementary and middle school buildings were found to be over 35 years old. - Aged school facilities pose problems that directly affect students' health and safety such as asbestos, lack of seismic resistance and hazardous urethane blend tracks. - Investment in school facilities could be effective not only in achieving its primary goal of improving health and safety but also in inducing secondary effects such as heightened academic performance. - A quality educational environment can have a positive influence on the attitudes and behaviors of both students and teachers. - Future investments in school facilities need to enhance quality and reflect the changes in the educational curriculum. - To raise the needed financial resources for investment, it is necessary to adjust the expenditure structure by item within the total education budget. - For efficient investment, a systemic and comprehensive system that can assess the educational environment must be formulated. - Future investment in school facilities should be made in light of the government's educational policy that fits the changing educational environment.
Keywords: 330